2011
DOI: 10.1017/s003118201100117x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic filariasis in children: Clinical features, infection burdens and future prospects for elimination

Abstract: S U M M A R YLymphatic filariasis (LF), a common parasitic infection in tropical countries, causes lymphoedema of limbs, hydrocele and acute attacks of dermato-lymphangio-adenitis. Recent advances in diagnosis have helped to recognize that LF infection is often acquired in childhood. Newly available diagnostic techniques like sensitive antigen and antibody assays, Doppler ultrasonography and lymphoscintigraphy have helped to understand the subclinical pathology caused by this infection, which was hitherto gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 47 publications
(104 reference statements)
0
20
0
Order By: Relevance
“…119,120 Usually, there is a long interval between acquiring the infection and development of disease manifestations. 121 Thus, even if the infection is acquired during childhood, the clinical disease is developed mostly during adult life. 122 Enlargement of lymph node or soft tissue swelling in the inguinal region, axilla, or neck is well known in pediatric age group.…”
Section: Lymphatic Filariasismentioning
confidence: 99%
See 1 more Smart Citation
“…119,120 Usually, there is a long interval between acquiring the infection and development of disease manifestations. 121 Thus, even if the infection is acquired during childhood, the clinical disease is developed mostly during adult life. 122 Enlargement of lymph node or soft tissue swelling in the inguinal region, axilla, or neck is well known in pediatric age group.…”
Section: Lymphatic Filariasismentioning
confidence: 99%
“…136 Imaging modalities such as ultrasonography, Doppler technique may also help in diagnosis. 121,137 Diethylcarbamazine citrate is the drug of choice with a standard dose of 6 mg/kg daily for 12 days. However, recent studies have shown that a single dose of 6 mg/kg is also at par.…”
Section: Lymphatic Filariasismentioning
confidence: 99%
“…Subclinical dilation and damage to lymphatic vessels can be detected in children using ultrasound or lymphoscintigraphy 43. In adults, progressive dilation of lymphatic vessels by nests of adult parasites, mainly in the lower extremities and genitals, results in clinical syndromes including acute lymphangitis, dermatolymphangioadenitis and lymphoedema, which progresses to elephantiasis in chronic cases.…”
Section: Lymphatic Filariasismentioning
confidence: 99%
“…Based on the Preventive Chemotherapy Databank, we have calculated that in 2011 there were 1.41 billion people living in high-risk areas for infection 15. Long thought to be an exclusive infection of adulthood, LF is now recognised to be an infection often contracted in childhood, with early manifestations of lymphatic obstruction, filarial fevers, and in some cases hydrocele and lymphoedema 4 5. Children under 10 years of age have prevalence rates around 30% of the adult prevalence rates, while those 10–19-years-old have approximately 69% of the adult prevalence rate 5.…”
Section: The Problem: Ntds In Childrenmentioning
confidence: 99%
“…Among the seven most common NTDs affecting impoverished populations in developing countries (table 1), ascariasis, trichuriasis, schistosomiasis and trachoma disproportionately affect children, whereas lymphatic filariasis (LF) and onchocerciasis mainly affect adult populations. However, there is evidence that the clinical manifestations of LF often begin silently in children,4 5 while hookworm infection affects both children and adults 6. One NTD that has seen resounding success in progress toward eradication is dracunculiasis (guinea worm infection), which through control programmes focusing on clean water, water treatment and health education, only 1058 cases were reported worldwide in 2011 7.…”
Section: Introductionmentioning
confidence: 99%